Ongoing child welfare services: Understanding the relationship of worker and organizational characteristics to service provision. (June 2018) - Lwin, Kristen; Fluke, John; Trocmé, Nico; Fallon, Barbara; Mishna, Faye
Abstract: Ongoing child welfare services are put in place after completion of the initial maltreatment investigation when there is a perceived need to mitigate the risk of future harm. The knowledge of how clinical, worker, and organizational characteristics interact with this decision to provide ongoing child welfare services is not well integrated in the research literature. Using secondary data from the Canadian Incidence Study of Reported Child Abuse and Neglect-2008, this study's primary objective is to understand the relationship of clinical, worker, and organizational characteristics to the decision to transfer a case to ongoing child welfare services and their relative contribution to the transfer decision in Canada. Findings indicate that several clinical level variables are associated with families receiving ongoing services. Additionally, organizational factors, such as type of services offered by the organization and the number of employee support programs available to workers, significantly predicted the decision to transfer a case to ongoing services. While no worker factors, such as education, amount of training, experience, or caseload, were associated with ongoing service receipt, the intraclass correlation coefficient of the final three-level parsimonious model indicated substantial clustering at the worker level. Results indicate that Canadian child welfare workers make decisions differently based on factors not available in the current study and that what would be deemed as important worker characteristics do not necessarily predict this outcome. Findings and implications for future research are discussed.